A high sensitivity method of closed-tube loop-mediated isothermal amplification developed for visual and rapid detection of cow milk adulteration. (April 2022) - Wang, Yifan; Yu, Zhezhe; Liu, Yongfeng
Abstract: A novel closed-tube loop-mediated isothermal amplification (LAMP) was developed to detect goat milk adulterated with cow milk. The reaction results of the LAMP assay developed, identified using both visual observation and agarose gel electrophoresis, were completely consistent, indicating that visual observation was suitable and efficient to judge the final LAMP results. The specificity of LAMP assay was evaluated using DNA of related species namely goat, pork, chicken, duck, dog, which revealed only a specific amplification of cow. The sensitivity of LAMP assay was as low as 10 fg. The limit of detection (LOD) of LAMP assay reached 0.01%, 10 times higher than PCR assay. In addition, this assay successfully amplified and identified 0.01% of cow commercial milk products in goat milk. Therefore, our results provided a simple, specific, sensitive, rapid, and cost-effective method to detect goat milk adulteration.